2018
DOI: 10.1152/ajplung.00215.2017
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 2A receptor inhibition protects against the development of pulmonary hypertension and pulmonary vascular remodeling in neonatal mice

Abstract: Pulmonary hypertension (PH) complicating bronchopulmonary dysplasia (BPD) worsens clinical outcomes in former preterm infants. Increased serotonin (5-hydroxytryptamine, 5-HT) signaling plays a prominent role in PH pathogenesis and progression in adults. We hypothesized that increased 5-HT signaling contributes to the pathogenesis of neonatal PH, complicating BPD and neonatal lung injury. Thus, we investigated 5-HT signaling in neonatal mice exposed to bleomycin, previously demonstrated to induce PH and alveola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 76 publications
1
30
1
Order By: Relevance
“…This may underlie the increased vasoconstriction seen with 5‐HT in the mesenteric arteries from the ENT4‐KO mice. A similar enhancement in 5‐HT constrictor activity is seen in pathological conditions (e.g., diabetes, pulmonary hypertension) that result in vascular damage (Delaney et al, 2018; MacLean, 2018; Watts & Davis, 2011). With respect to other genes examined, it was the male ENT4‐KO mice that showed the most extensive changes (relative to male WT), and mostly in those genes related to adenosine metabolism (i.e., increased ADK, ADA, ENT1, ENT2, and CNT2).…”
Section: Discussionmentioning
confidence: 67%
“…This may underlie the increased vasoconstriction seen with 5‐HT in the mesenteric arteries from the ENT4‐KO mice. A similar enhancement in 5‐HT constrictor activity is seen in pathological conditions (e.g., diabetes, pulmonary hypertension) that result in vascular damage (Delaney et al, 2018; MacLean, 2018; Watts & Davis, 2011). With respect to other genes examined, it was the male ENT4‐KO mice that showed the most extensive changes (relative to male WT), and mostly in those genes related to adenosine metabolism (i.e., increased ADK, ADA, ENT1, ENT2, and CNT2).…”
Section: Discussionmentioning
confidence: 67%
“…We previously reported that pharmacologic blockade of the 5‐HT 2A R prevents bleomycin‐induced PH and pulmonary vascular remodeling (Delaney et al, 2018). As platelets contain 99% of circulating 5‐HT, which is released upon activation, we tested the hypothesis that circulating platelets are activated and increased in the lungs of neonatal mice with bleomycin‐induced PH.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning on days 1-2 of life, C57BL/6 wild-type mice (Jackson Laboratory) were injected with intraperitoneal phosphate-buffered saline (PBS) or bleomycin (3 units/kg, dissolved in PBS) (Hospira) three times per week for 3 weeks (total nine injections, 10 μl). This murine injury model of PH and BPD produces similar major pathologic findings to infants with PH and BPD including; impaired alveolar development (decreased radial alveolar counts, increased mean linear intercept and increased air space area), vascular remodeling (decreased vessel density, muscularization of small vessels, medial wall thickening), and PH (right ventricular hypertrophy and elevated right ventricular systolic pressure Delaney et al, 2018;Delaney et al, 2015;Sherlock et al, 2018). Bleomycin doses were adjusted for body weight at each injection.…”
Section: Mouse Modelmentioning
confidence: 99%
See 2 more Smart Citations